THE APOLOGY OF CHRISTIAN UNDERSTANDING OF HAPPINES IN JOSEPH RATZINGER’S THEOLOGICAL REFLEXION - Kozakiewicz, Martyna (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
Since the dawn of time, people have attempted to answer fundamental questions about their existence. One of the topics that philosophers, thinkers and theologians have dealt with since the very beginning of civilization is the experience of happiness. Depending on the era and the adopted thought system, happiness was defined in a completely different way. Greek philosophers, Jewish religion thought, and contemporary social and philosophical trends, such as materialism or anarchism, had different views on this subject. But what does theology have to say about happiness? What are the characteristics of the Christian understanding of happiness, what makes it unique and what is it based on? Finally, how the credibility and rationality of the Christian message of happiness can be shown? The article is an attempt to answer the following questions, taking as sources selected works of Joseph Ratzinger, whose teaching about happiness is not only extremely deep and interesting, but also has an undeniably apologetic value.